The Correlation Between Vocabulary Mastery And Self Esteem On Students’ Speaking Skill - Nurmala Dewi; Jimmi Jimmi (Wanastra: Jurnal Bahasa dan Sastra, 2018)
Abstract - The purpose of this research was to find out whether there is a  significant  correlations between  vocabulary mastery and self esteem on students’ speaking skill. The population of this study was X grade students majoring in natural science at SMU 64 Jakarta Timur, while the sample was 60 students  were chosen randomly from those 3 classes. The writer used three instruments to gain the data :  a vocabulary test,  a speaking test, and a self esteem questionnaire.  A quantitative analysis that included descriptive statistic and the correlation and regression analysis tests were conducted to answer the research hypotheses. The research results found that  there is a significant simultaneous correlation between vocabulary mastery and self esteem on students’ speaking skill. This finding has proved  the views which are vocabulary as a main language component and self esteem as affective factor have contributions in developing learning language especially fon speaking skill.  Key words : Vocabulary Mastery, Self Esteem, Speaking Skill